Proof of Coercion and Fraud in the Making of Notarial Deeds Case Study of South Jakarta District Court Decision Number 321/Pdt.G/2016/PN. Jkt. Cell - Sumartini, Sumartini (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
An agreement is one of the sources of engagement regulated in Chapter II of Book 3 of the Civil Code which can be stated in the form of a Notarial Deed. Authentic deeds clearly stipulate rights and obligations, providing legal certainty. In dispute resolution, authentic deeds function as the strongest written evidence. However, even with perfect evidentiary power, a Notarial Deed cannot be separated from efforts to cancel the contract. Some of the reasons for cancellation are due to defects in the agreement due to elements of coercion and/or elements of deception as stated by the Plaintiff in South Jakarta District Court Decision Number 321/Pdt.G/2016/PN. Jkt. Cell. Based on the research results, the Plaintiff is obliged to provide clear evidence. When compared with the Plaintiff's evidence, the evidence presented by the Plaintiff is not sufficient to prove the argument of coercion or fraud because the Plaintiff's Witnesses did not know that the Plaintiff and the Defendants had entered into a Sale and Purchase Agreement. In the process or attempt to cancel a notarial deed, the evidence must be clear and in such a way that the party who has the notarial deed does not need other evidence to state the truth of the notarial deed. With this formulation, the judge no longer needs to test its truth or in other words, an authentic deed has perfect evidentiary power both physically and materially.